2020
DOI: 10.1093/jxb/eraa017
|View full text |Cite
|
Sign up to set email alerts
|

Aphid fecundity and defenses in wheat exposed to a combination of heat and drought stress

Abstract: Plants are routinely subjected simultaneously to different abiotic and biotic stresses, such as heat, drought, and insect infestation. Plant–insect interactions in such complex stress situations are poorly understood. We evaluated the performance of the grain aphid (Sitobion avenae) in wheat (Triticum aestivum L.) exposed to a combination of heat and drought stresses. We also performed assays of the relative water content, nutritional quality, and responses of phytohormone signaling pathways. Lower relative wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 62 publications
5
47
0
Order By: Relevance
“…7). This finding is consistent with our prediction and is supported by a large body of literature reporting elevated plant defence and decreased plant growth and vigour under drought stress (Templer et al, 2017;Beetge & Krüger 2019;Xie et al, 2020), indicating that these plant responses mediate the impact of drought stress on sap-feeding insect herbivores. These changes could be caused by increased contact between aphids and plant defensive compounds, a reduction in the availability of nutrients in the phloem sap, or/and a reduction in the growth and development of new plant tissue which is often the preferred feeding site for many aphid species, although this can differ between aphid-plant combinations (Leather & Dixon, 1981).…”
Section: Plant Vigour Could Explain Drought Stress Effects On Aphid Fsupporting
confidence: 93%
“…7). This finding is consistent with our prediction and is supported by a large body of literature reporting elevated plant defence and decreased plant growth and vigour under drought stress (Templer et al, 2017;Beetge & Krüger 2019;Xie et al, 2020), indicating that these plant responses mediate the impact of drought stress on sap-feeding insect herbivores. These changes could be caused by increased contact between aphids and plant defensive compounds, a reduction in the availability of nutrients in the phloem sap, or/and a reduction in the growth and development of new plant tissue which is often the preferred feeding site for many aphid species, although this can differ between aphid-plant combinations (Leather & Dixon, 1981).…”
Section: Plant Vigour Could Explain Drought Stress Effects On Aphid Fsupporting
confidence: 93%
“…Such results were found for Brevicoryne brassicae L. and Myzus persicae Sulzer, which reproduced better on plants of Brassica oleracea (Brassicaceae) under constant medium drought than on control plants or plants experiencing severe or pulsed drought (Tariq, Wright, Rossiter, & Staley, 2012). Aphids of S. avenae on T. aestivum plants under drought stress (10% SWC) had a reduced performance compared to those on non‐stressed plants (20% SWC), which may have been related to an upregulation of phytohormone‐regulated defense responses in the plants (Xie et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in the same context as those obtained by Varsani et al (2019) who indicated that leaf aphids population was significantly higher on benzoxazinoids-deficient maize plants. Also, Xie et al (2020) reported that there were lower net reproductive rates of aphids, intrinsic rates of increase and finite rates of increase under drought stress compared with aphids reared on plants in the absence of stress.…”
Section: Iv-insect Infestation 1-maize Crop A-applied Irrigation Water Levelsmentioning
confidence: 99%